2011
DOI: 10.1530/erc-11-0074
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor and cancer

Abstract: The widespread epidemic of obesity and type 2 diabetes has raised concern for the impact of these disorders as risk factors for cancer and has renewed the interest for studies regarding the involvement of hyperinsulinemia and insulin receptor (IR) in cancer progression. Overexpression of IR in cancer cells may explain their increased sensitivity to hyperinsulinemia. Moreover, IR isoform A (IR-A) together with autocrine production of its ligand IGF2 is emerging as an important mechanism of normal and cancer ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
229
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(238 citation statements)
references
References 179 publications
(146 reference statements)
3
229
0
6
Order By: Relevance
“…Insulin, a key mediator of important metabolic functions, coordinates and regulates the storage and release of the body's fuel (Belfiore & Malaguarnera 2011). Insulin, which is secreted by b-cells of the pancreas in response to increasing blood glucose levels, binds to the cognate receptor (INSR) mainly expressed by hepatocytes, adipocytes, and muscle cells as well as prostate and breast tissues (Belfiore & Malaguarnera 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Insulin, a key mediator of important metabolic functions, coordinates and regulates the storage and release of the body's fuel (Belfiore & Malaguarnera 2011). Insulin, which is secreted by b-cells of the pancreas in response to increasing blood glucose levels, binds to the cognate receptor (INSR) mainly expressed by hepatocytes, adipocytes, and muscle cells as well as prostate and breast tissues (Belfiore & Malaguarnera 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin, which is secreted by b-cells of the pancreas in response to increasing blood glucose levels, binds to the cognate receptor (INSR) mainly expressed by hepatocytes, adipocytes, and muscle cells as well as prostate and breast tissues (Belfiore & Malaguarnera 2011). So far, two INSR isoforms have been identified, isoform A (INSR-A) and isoform B (INSR-B), which are usually co-expressed and regulated by several factors (Belfiore 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, IGF‐1 mainly originates in the liver and shows low inter‐individual variability in its circulating levels 4. Binding of ligand to the IGF‐1 receptor (IGF1R) leads to the phosphorylation of Src homology 2 domain‐containing (SHC)‐transforming protein and subsequent activation of the Ras pathway, and phosphorylation of insulin receptor substrate (IRS)‐1 protein, which induces the activation of the phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) pathway 5. The relationship between serum IGF‐1 level and prostate cancer is of interest because previous studies have suggested that aspects of energy metabolism and balance are associated with the incidence of prostate cancer,6 and the effect of environmental factors on prostate cancer risk may be mediated by differences in the concentrations of substances including testosterone and prostate‐specific antigen (PSA) 7…”
Section: Introductionmentioning
confidence: 99%